2016
DOI: 10.1371/journal.pone.0162461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Intervention with Sodium Butyrate on Gut Microbiota and the Expression of Inflammatory Cytokines in Neonatal Piglets

Abstract: Butyrate in the gut of animals has potential properties including regulating the innate immune, modulating the lipid metabolism, and protecting gut healthy. So far, only limited information on the impact of butyrate on the neonatal is available. This study aimed to investigate effects of oral administration of sodium butyrate (SB) on gut microbiota and the expression of inflammatory cytokine in neonatal piglets. Ten litters of crossbred newborn piglets were randomly allocated to the SB and control (CO) groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 57 publications
5
67
1
Order By: Relevance
“…In patients with Crohn's disease, butyrate decreases the expression of pro-inflammatory cytokines [24]. As shown in the study by Xu et al, early intervention with sodium butyrate modulates the inflammatory cytokine profile in the ileum of neonatal piglets [25]; notably, sodium butyrate effectively suppressed the expression of mRNA encoding the pro-inflammatory cytokine TNF-α in piglet colon tissue. Thus, sodium butyrate exerts positive effects on alleviating diarrhea and reducing inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…In patients with Crohn's disease, butyrate decreases the expression of pro-inflammatory cytokines [24]. As shown in the study by Xu et al, early intervention with sodium butyrate modulates the inflammatory cytokine profile in the ileum of neonatal piglets [25]; notably, sodium butyrate effectively suppressed the expression of mRNA encoding the pro-inflammatory cytokine TNF-α in piglet colon tissue. Thus, sodium butyrate exerts positive effects on alleviating diarrhea and reducing inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…Butyrate, modulates inflammatory processes by inhibiting the activity of NF‐κB and HDAC1, and affects gene expression in colonic epithelial cells (Xu et al ., ). We also previously showed that butyrate downregulates HDAC1 and proinflammatory cytokines, and upregulates the expression of anti‐inflammatory cytokines in the gut (Xu et al ., ). Compared to butyrate, propionate exerts an equipotent effect, at suppressing the NF‐κB reporter activity, immune‐related gene expression and cytokine release in vitro (Tedelind et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Anti‐inflammatory functions of SCFAs have been extensively investigated, particularly butyrate, which has been shown to have an important role in inhibiting inflammatory process. Maslowski and colleagues () and Xu and colleagues () have shown that butyrate upregulated the expression of anti‐inflammatory cytokines and downregulated proinflammatory agents in the intestinal epithelium. In addition to acting as signalling molecules, SCFAs also maintain the balance of intestine microbial ecosystem, which contributes to gut immune development (Lee and Mazmanian, ; Chung et al ., ; Kamada et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations